Impact of Intracranial Aneurysm Morphology and Rupture Status on the Particle Residence Time. Issue 4 (19th April 2019) - Leemans, E.L.; Cornelissen, B.M.W.; Rosalini, G.; Verbaan, D.; Schneiders, J.J.; van den Berg, R.; Vandertop, W.P.; van Bavel, E.T.; Slump, C.H.; Majoie, C.B.L.M.; Marquering, H.A.
ABSTRACT: BACKGROUND AND PURPOSE: Aneurysm hemodynamics play an important role in aneurysm growth and subsequent rupture. Within the available hemodynamic characteristics, particle residence time (PRT) is relatively unexplored. However, some studies have shown that PRT is related to thrombus formation and inflammation. The goal of this study is to evaluate the association between PRT and aneurysm rupture and morphology. METHODS: We determined the PRT for 113 aneurysms (61 unruptured, 53 ruptured) based on computational fluid dynamic models. Virtual particles were injected into the parent vessel and followed during multiple cardiac cycles. PRT was defined as the time needed for 99% of the particles that entered an aneurysm to leave the aneurysm. Subsequently, we evaluated the association between PRT, rupture, and morphology (aneurysm type, presence of blebs, or multiple lobulations). RESULTS: PRT showed no significant difference between unruptured (1.1 seconds interquartile range [IQR .39‐2.0 seconds]) and ruptured aneurysms (1.2 seconds [IQR .47‐2.3 seconds]). PRT was influenced by aneurysm morphology. Longer PRTs were seen in bifurcation aneurysms (1.3 seconds [IQR .54‐2.4 seconds], P = .01) and aneurysms with blebs or multiple lobulations (1.92 seconds [IQR .94‐2.8 seconds], P < .001). Four of five partially thrombosed aneurysms had a long residence time (>1.9 seconds). CONCLUSIONS: Our study shows an influence of aneurysm morphology on PRT. Nevertheless, it suggests that PRT cannot be used to differentiate unruptured and ruptured aneurysms.